Interaural attention modulates outer hair cell function - Srinivasan, Sridhar (Eur J Neurosci, 2014)
Mounting evidence suggests that auditory attention tasks may modulate the sensitivity of the cochlea by way of the corticofugal and the medial olivocochlear (MOC) efferent pathways. Here, we studied the extent to which a separate efferent tract, the “uncrossed” MOC, which functionally connects the two ears, mediates inter-aural selective attention. We compared distortion product otoacoustic emissions (DPOAEs) in one ear to binaurally-presented primaries, using an intermodal target detection task in which participants were instructed to report the occurrence of brief target events (visual changes, tones). Three tasks were compared under identical physical stimulation: (1) report brief tones in the ear in which DPOAE responses were recorded; (2) report brief tones presented to the contralateral, non-recorded ear; (3) report brief phase shifts of a visual grating at fixation. Effects of attention were observed as parallel shifts in overall DPOAE contour level, with DPOAEs relatively higher in overall level when subjects ignored the auditory stimuli and attended to the visual stimulus, compared with both of the auditory-attending conditions. Importantly, DPOAE levels were statistically lowest when attention was directed to the ipsilateral ear in which the DPOAE recordings were made. These data corroborate notions that top-down mechanisms, via the corticofugal and medial efferent pathways, mediate cochlear responses during intermodal attention. New findings show attending to one ear can significantly alter the physiological response of the contralateral, unattended ear, likely through the uncrossed-medial olivocochlear efferent fibers connecting the two ears.